Carbon capture and utilization via calcium looping, sorption enhanced methanation and green hydrogen: A techno-economic analysis and life cycle assessment study. (15th November 2022) - Chirone, Roberto; Paulillo, Andrea; Coppola, Antonio; Scala, Fabrizio
Graphical abstract: Highlights: TEA and LCA of CaL and SEM integrated process for CO2 capture & utilization. The process has the advantage of avoiding a costly ASU for CaL. LCA highlighted several environmental trade-offs. Production cost for methane is higher than for natural gas but lower than for biomethane. PEM electrolyzer accounts for most of the costs and environmental impacts of the process. Abstract: The production of synthetic methane using CO2 from flue gases and green hydrogen appears to be a promising way to combine the concepts of renewable energy, chemical storage, and utilization of CO2 . Recently, a new reactor configuration for catalytic methanation has been proposed, integrating sorption-enhanced methanation and chemical looping in interconnected fluidized bed systems. This configuration would ensure high methane yields while keeping good temperature control and low operating pressure. In this work, such novel system layout for the catalytic production of methane was combined with a calcium looping unit for CO2 capture from flue gases of a coal-fired power plant, and with a water electrolyzer sustained by renewable energy. The integrated layout offers a series of advantages deriving from the integration of different mass and energy flows of the different sections of the plant. The performance of this latter was assessed in terms of construction and production costs, as well as from an environmental point of view: a life cycle assessment was carried out to quantify the environmental impact of all process units. Results of the techno-economic analysis indicated that the production cost of methane is higher than that of natural gas (0.66 vs 0.17 €/Nm 3 ), but lower than that of biomethane (1 €/Nm 3 ). The largest impact on such costs comes from the PEM electrolyzer. The LCA analysis showed that the environmental performance is better in some categories and worse in others with respect to traditional scenarios. Again, the PEM electrolyzer appears to account for most of the environmental impacts of the process.